Suppressing crucial oncogenes of leukemia initiator cells by major royal jelly protein 2 for mediating apoptosis in myeloid and lymphoid leukemia cells. Issue 17 (5th August 2022) - Abu-Serie, Marwa M.; Habashy, Noha H.
Abstract : Apis mellifera major royal jelly protein 2 suppressed leukemia-initiating stem cell (LIC)-related oncogenes, MMP10 and HDAC8 activities, as well as CD34 + LICs in myeloid and lymphoid leukemia cells, resulting in their cell cycle arrest and apoptosis. Abstract : Relapse of leukemia and drug resistance are still the major obstacles to therapy due to leukemia-initiating stem/progenitor cells (LICs); thus, targeting them using safe compounds is crucial. Here, we evaluated the anti-leukemic effect of royal jelly (RJ) components, which had a higher safe concentration (EC100 values) than the chemotherapeutic drug doxorubicin (DOX). The RJ-protein fraction 50 (PF50, precipitated at 40–50% ammonium sulfate saturation) and its constituents, major RJ protein (MRJP) 2 and its isoform X1, exhibited the highest growth inhibitory effect against myeloid NFS-60 and lymphoid Jurkat cell lines. MRJP2 has a nanosize, which may be the reason for its higher anti-leukemic activity than its isoform. These RJ proteins, particularly MRJP2, suppressed LIC-associated oncogenes (GATA2 and Evi-1) and eliminated CD34 + LICs, in contrast to the low anti-LIC efficacy of DOX. MRJP2 demonstrated higher apoptotic activity than its isoform by upregulating p53 and p21-mediated cell cycle arrest. This study also reported the potent inhibitory effect of RJ-proteins on matrix metallopeptidase 10 (metastatic marker) and histone deacetylase 8 (mediates LIC survival) activities. Thus, MRJP2 can be considered a promising novel therapeutic agent for both myeloid and lymphoid leukemia.